PEREMPUAN LESBIAN: IDENTIFIKASI PENYEBAB DAN METODE BIMBINGAN - Verolyna, Dita; Kurnia Syaputri, Intan; Warsah, Idi (UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to identify the factors that cause women to become lesbi actors and the appropriate counseling guidance approach. This study uses a qualitative method with a phenomenological approach. Four lesbians in Rejang Lebong Regency, Bengkulu Province, were used as informants using in-depth interview techniques. The informants consisted of two butch lesbians and two femme lesbians. Based on the results of the interviews, it was found that there is no single factor that causes women to become lesbi actors. Many factors influence. The influence of hormones only occurs in butch type lesbians and heterosexual relationship trauma only occurs in femme type lesbians. Multifactor other than that is the lack of family attention, religious knowledge and wrong association. The characteristics of the butch type lesbian are very masculine and assertive and are not ashamed to show their identity. Contrary to women who prefer to hide and seem to cover up. The group guidance method can only be done for butch type lesbians while personal guidance must be done for the femme type. Both types of guidance can be done directly. Guidance is done by first introducing and listening more. This research does not look at the final product of the mentoring process but only focuses on identifying appropriate guidance methods based on the type of lesbian. Therefore future researchers can use the PAR method to see the success of the guidance process for both types of lesbians. Keywords: Lesbian, Counseling Guidance, Women, Sexual Orientation